FUTURE DATA ENTRY PROCESSING WITH ARTIFICIAL INTELLIGENCE - Dinda Putri Sananta; Agung Juliarto; Frank Gruben; Kees Tesselhof (Diponegoro Journal of Accounting, 2025)
Artificial Intelligence (AI) is reshaping the industry by automating routine tasks, transforming skill requirements, and raising ethical concerns. The study employs a qualitative research approach, analyzing academic literature, case studies, and secondary data to explore how AI is reshaping accounting job roles, influencing skill sets, and presenting ethical challenges. The findings highlight the increasing automation of tasks like data entry and financial reconciliation, necessitating a shift towards analytical and strategic roles for accountants. Additionally, the study emphasizes the growing importance of data analytics, critical thinking, and ethical decision making skills in an AI-driven environment. The research concludes by discussing the need for organizations to implement robust workforce development strategies and ethical frameworks to navigate the complex landscape of AI in accounting.